2019
DOI: 10.1167/tvst.8.3.24
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluoric Acid and Other Impurities in Toxic Perfluorooctane Batches

Abstract: Purpose: The complications with cytotoxic perfluorooctane (PFO) batches reported in 2015 were attributed to reactive underfluorinated impurities whose chemical identity and behavior still need to be clarified. Material and Methods: We analyzed original packaged samples of Alatocta batches involved in several reported cases of retinal toxicity. (A) The impurity profile was determined. (B) pH and fluoride ion content were measured. (C) Extraction with olive oil was performed to investigate differences in lipophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Because the safety threshold of protonated impurity in PFCL for intraocular use was unknown, they sought to obtain liquid of the highest grade corresponding to protonated impurity content < 0.1 ppm and equivalent to the detection limit of the method. 16 The work of Sparrow et al, 22 demonstrated the toxicity of 1H-PFO at the perfluorocarbon-fluid interface in tissue culture by a qualitative assessment. These studies 7 , 22 indicated the level of impurities that were used for approval of perfluoro-n-octane from the U.S. Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the safety threshold of protonated impurity in PFCL for intraocular use was unknown, they sought to obtain liquid of the highest grade corresponding to protonated impurity content < 0.1 ppm and equivalent to the detection limit of the method. 16 The work of Sparrow et al, 22 demonstrated the toxicity of 1H-PFO at the perfluorocarbon-fluid interface in tissue culture by a qualitative assessment. These studies 7 , 22 indicated the level of impurities that were used for approval of perfluoro-n-octane from the U.S. Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to analyses of the contaminant profiles of the toxic AlaOcta batches conducted by Menz et al, 16 we might affirm that the toxicity of those batches could not be solely related to the presence of 1H-PFO or DFH, because their concentrations, which differed between the 59 and 875 ppm for 1H-PFO and between 29 and 45 ppm for DFH, were well below the cytotoxicity limit (CC 30 ) calculated in this study (CC 30 : 55712 ppm for 1H-PFO and 1173 ppm for DFH). Instead, the PFO batches containing PFOA at concentrations varying between 50 and 700 ppm and a mix of p -xylene isomers/ethylbenzene (82%:18% ratio) at 5 to 30 ppm 16 were surely toxic, because the quantity of these compounds was well above the cytotoxic limit found in this study (CC 30 : 17 ppm for PFOA; 1.21 ppm for p -xylene and 1.06 ppm for ethylbenzene). In addition, Srivastava et al 17 also analyzed the contaminants in the toxic AlaOcta batches and found that DFH was contained at nontoxic concentration, whereas PFOA was detected at concentrations that reduced the ARPE-19 cell viability of > 70% and thus were inevitably cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unlikely that the observed impurities are introduced through the PFO itself, because the only PFO-based impurities potentially detectable by XRR and NR would be under-fluorinated (i.e., partially hydrogenated) molecules of amphiphilic character, which are not among the common impurities in PFO [69]. Moreover, there is considerable variability between the different samples regarding the obtained density deficits D and adsorbed amounts DHC even though PFO was introduced into the measurement cells from the same original bottle for samples 1, 2, and 4.…”
Section: Results and Discussionmentioning
confidence: 99%